2009
DOI: 10.2174/1874282300903010196
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Daily Rainfall Intensity Over Israel 1950/1-2003/4

Abstract: Abstract:The study focuses on long-term trends of daily rainfall in Israel as a function of their intensity in order to identify potential trends in rainfall extremity. The study period is the rainy season, October-May between 1950/1 and 2003/4. For the total rainfall, an increased trend is shown across Israel, especially for the central and southern regions, though non-significant. Daily rainfall intensity showed non-significant trends of increase in the heavy rainfall at the center and south and decrease at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
26
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 23 publications
4
26
0
Order By: Relevance
“…Spatially, there is a decreasing trend of rainfall from the northwest towards the east and south east. Mean annual rainfall and mean maximum daily rainfall are increasing but statistically not significant in two stations (RAS and JOU) in the subhumid zone and this is consistent with the findings with similar nearby subhumid regions such as central western parts of the Jordan river (Alpert et al, 2002;Wettenberg et al, 2007;Yusef et al, 2009). Mean annual rainfall in the semi-arid zone shows a general nonsignificant decreasing trend and this agrees with some earlier studies which reported nonsignificant decrease in mean daily and monthly rainfall (Freiwan and Kadioglu, 2008a;2008b;Ghanem, 2011).…”
Section: Discussionsupporting
confidence: 91%
“…Spatially, there is a decreasing trend of rainfall from the northwest towards the east and south east. Mean annual rainfall and mean maximum daily rainfall are increasing but statistically not significant in two stations (RAS and JOU) in the subhumid zone and this is consistent with the findings with similar nearby subhumid regions such as central western parts of the Jordan river (Alpert et al, 2002;Wettenberg et al, 2007;Yusef et al, 2009). Mean annual rainfall in the semi-arid zone shows a general nonsignificant decreasing trend and this agrees with some earlier studies which reported nonsignificant decrease in mean daily and monthly rainfall (Freiwan and Kadioglu, 2008a;2008b;Ghanem, 2011).…”
Section: Discussionsupporting
confidence: 91%
“…Samuels et al (2017) have evaluated the ability of 23 models, participating in the Coupled Model Intercomparison Project phase 5 (CMIP5), to predict extreme precipitation indices (EPI) in the 21st century over the EM. Such a trend has been shown over the Mediterranean region for the second half of the 20th century (Alpert et al, 2002;Zhang et al, 2005;Yosef et al, 2009;Ziv et al, 2014), though insignificant for the Middle East and Israel, attributed to the high inter-annual variability of precipitation in this region. These overestimations were related to the inadequate representation of topography in the GCMs, due to relatively coarse spatial resolutions.…”
Section: Introductionmentioning
confidence: 76%
“…The comparison between NAO and EATL/WRUS, in Israel, gives an indication that both of them have the same influence on total precipitation. These results are also in line with previous ones which found a link between Israel rainfall and both NAO and EATL/WRUS patterns with maximum precipitation taking place during their positive phases (Krichak and Alpert, ; ; Yosef et al ., ). During the positive phase of the EATL/WRUS, our results show high precipitation amounts in the EM, North Africa, eastern Turkey and Sicily, while this relationship is reversed in the western, central Mediterranean and central parts of Europe.…”
Section: Resultsmentioning
confidence: 99%